2014
DOI: 10.1007/s00247-014-2909-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acoustic noise in a neonatal intensive care unit MRI system

Abstract: Background To eliminate the medical risks and logistical challenges of transporting infants from the neonatal intensive care unit (NICU) to the radiology department for magnetic resonance imaging, a small-footprint 1.5-T MRI scanner has been developed for neonatal imaging within the NICU. MRI is known to be noisy, and exposure to excessive acoustic noise has the potential to elicit physiological distress and impact development in the term and preterm infant. Objective To measure and compare the acoustic nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
0
31
0
Order By: Relevance
“…A small-footprint 1.5-T orthopedic MRI scanner (ONI Medical Systems, currently GE Healthcare, Waukesha, WI) was previously adapted for clinical use in our NICU (17)(18)(19); the scanner's 18-cm bore can accommodate infants weighting up to approximately 4,000 g. Using this scanner, standard axial three-dimensional fast gradient echo (FGRE) images were acquired in all 18 patients (repetition time/echo time [TR/TE] z7/1.9 ms; 10 8 flip angle; 18-20 cm field of view; 3 mm slice thickness; 5-10 averages). Additionally, fast spin echo (FrFSE) images were acquired for 10 patients (TR/TE 3,000/11.6 ms; 16 cm field of view; 3 mm slice thickness; echo train length 5) and Propeller images (TR/TE 3,750/32.5 ms; 16 cm field of view; 3 mm slice thickness; echo train length 10) were acquired for 11 patients.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small-footprint 1.5-T orthopedic MRI scanner (ONI Medical Systems, currently GE Healthcare, Waukesha, WI) was previously adapted for clinical use in our NICU (17)(18)(19); the scanner's 18-cm bore can accommodate infants weighting up to approximately 4,000 g. Using this scanner, standard axial three-dimensional fast gradient echo (FGRE) images were acquired in all 18 patients (repetition time/echo time [TR/TE] z7/1.9 ms; 10 8 flip angle; 18-20 cm field of view; 3 mm slice thickness; 5-10 averages). Additionally, fast spin echo (FrFSE) images were acquired for 10 patients (TR/TE 3,000/11.6 ms; 16 cm field of view; 3 mm slice thickness; echo train length 5) and Propeller images (TR/TE 3,750/32.5 ms; 16 cm field of view; 3 mm slice thickness; echo train length 10) were acquired for 11 patients.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Pulmonary MRI of the neonate is additionally confounded by small patient size and the delicate nature of transporting a NICU patient to the scanner. To overcome the latter two challenges, we extend the application of a unique, small footprint 1.5-T MRI scanner designed by our colleagues in the Imaging Research Center at Cincinnati Children's Hospital for installation and clinical use in our NICU (17)(18)(19) to image neonatal lungs. Using this scanner, commercial MRI sequences, and quantitative analysis, we demonstrate the ability of MRI to spatially map and quantify lung pathology associated with premature birth in quietly breathing neonates.…”
mentioning
confidence: 99%
“…A second report from the Hammersmith team specific to neonates with BPD found higher relative proton density in BPD patients versus controls and described 2 types of parenchymal abnormalities in BPD infants: focal high-density areas and low-density, cystlike abnormalities. 43 Colleagues at Cincinnati Children's Hospital Medical Center designed and modified a small-footprint 1.5-T orthopedic MRI scanner for use in the authors' NICU, [44][45][46] and they recently reported success imaging nonsedate, free-breathing BPD patients using this scanner and standard MRI pulse sequences. 47 Stark and significant differences in parenchymal signal intensity were observed in the BPD patients compared with full-term control NICU patients (Fig.…”
Section: Conventional 1 H Mrimentioning
confidence: 97%
“…(207-209) The FDA also requires that the “A-weighted root mean square (rms) sound pressure level [not exceed] 99 dBA with hearing protection in place.”(1,177,178) As a result of these limits, and despite the fact that there are no specific guidelines about the use and type of hearing protection applied during MRI, passive hearing protection is used on all neonates undergoing MRI examination. (210) In the case of the fetus, multiple studies have demonstrated that the gravid uterus provides an acceptable barrier for sound attenuation, and that sound generated by MRI during in utero imaging would not be harmful to the fetal ear. (211-216)…”
Section: Improvements and Implications Of Increased Magnetic Field Stmentioning
confidence: 99%
“…(22,23) Tkach et al also demonstrated that lower noise levels produced by NICU magnets were less disruptive to the neonates sleep, which is better developmentally, and increases the likelihood that an exam can be completed without the use of sedation. (210) One limitation of NICU scanners is the inability to accommodate larger patients, as demonstrated by the magnet used by Tkach et al which was able to accommodate neonates weighting 4.5kg or less. These size restrictions may limit the use of a NICU magnet in critically ill full-term infants.…”
Section: Neonatal Imagingmentioning
confidence: 99%